ENGAGING AND COLLABORATING IN THE COMMUNITY OF PRACTICE - Erkaboyeva Saodathon (American Journals Publishing, 2023)
In this article, continuous professional development through community of practice will be discussed
Keywords: continuous professional development (CPD), community of practice (CoP), mentoring